P127 Optical diagnosis training to improve dysplasia characterisation in inflammatory bowel disease (OPTIC-IBD): a multicentre RCT. (19th June 2022) - Iacucci, M; Ingram, RJM; Bazarova, A; Cannatelli, R; Labarile, N; Nardone, O; Parigi, T; Siau, K; Smith, S; Ghosh, S
Abstract : Introduction: Endoscopic surveillance is performed in inflammatory bowel disease (IBD) to detect dysplasia. However, chronic inflammation alters mucosal and vascular colonic architecture, complicating lesion recognition. Optical diagnosis enhances our ability to accurately characterise IBD-associated dysplasia but such training is not readily available. We aim to fill this gap by developing and validating the new OPTIC-IBD online training platform (NCT04924543, funding GutsUK TRN2019-03). Methods: We designed an interactive, self-directed, multi-modality learning module. This includes surveillance principles, optical diagnosis methods, characterisation approach, classifications (SCENIC, Kudo, FACILE), examples and self-assessments. We invited participants from Canada, Italy and UK, including novice (<100 lifetime colonoscopies), intermediate and experienced endoscopists (≥1000). Assessments comprised 24 short endoscopic videos of IBD colonic lesions, divided into 8 non-dysplastic and 16 dysplastic lesions. Participants classified lesions, predicted histology and rated their confidence. All participants completed online training and feedback. Videos were repeated in a random order after ≥7 days. Participants were then randomised 1:1 to get feedback and extra training. All had a final assessment at 60 days with prior/new videos and similar case mix. We report diagnostic performance for dysplasia, interrater reliability and rater confidence. Results: We present a planned interim analysis of 77 participants after pre- and post-course assessments ( table 1 ). Diagnostic accuracy improved (primary endpoint: 44.5 to 54.0%, P <0.0001), particularly for novice and intermediate endoscopists. Sensitivity for dysplasia increased (50.3 to 59.1%) in line with prior experience. Specificity and accuracy were most improved for high confidence diagnoses (44.9 to 70.3% and 55.0 to 64.6%). In multilevel logistic regression, training was associated with correct diagnoses for high confidence (OR 1.40, 1.13–1.77) but not low confidence ratings (OR 1.09, 0.96–1.25). Training improved precision between participants and their confidence. Conclusions: The OPTIC-IBD training module improved participants' accuracy, precision and confidence in the optical diagnosis of IBD-associated dysplasia.